Age-age Correlation Models for Dalbergia sissoo Roxb. in Semi-arid Region of Central India - Rizvi, R. H.; Gupta, V. K.; Ahlawat, S. P.; Datta, A. (Indian Forester, 2009)
Nine years growth data of Dalbergia sissoo progeny trial established in semi-arid region of Central India was analysed. Significantly high age-age correlations were found for tree traits viz. height, dbh and D2H. Among three traits, empirical model developed for trait index D2H was found to be best fit (adj. R2 = 0.931). Using this model, the age-age correlations were predicted and efficiency of early selection in terms of gain per year for different plantation and rotation ages was estimated. For the selection age 12 years and rotation age 40 years, the genetic gain was almost twice. But this model is time dependent and does not take into account the growth rates. Another type of model based on variance ratio and a factor of relative size dependent growth was also applied. Predictions of age-age correlations were found to be better in case of D2H than height and dbh. According to this model, selection of progenies at 9 years age seems reasonably good for the improvement of height of Dalbergia sissoo.